Preseason in soccer: a paradox between a high volume of technical/tactical training and improvement in the neuromuscular performance of elite women soccer players - Kobal, R.; Carvalho, L.; Abad, C. C.; Faust, B.; Rossetti, M.; Saito, T.; Klosterhoff, R. R.; de Souza, E. O.; Barroso, R. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: There is a paradox between the development of strength-power abilities and the high volume of technical/tactical training in elite soccer players during the preseason. This concurrent effect between aerobic and neuromuscular training regimes induce impairment in power performance. METHODS: This study aimed to investigate the effect of an equalized program of strength-power training (4-5 sessions/week) and soccer training (4-6 sessions/week) in power and aerobic performance during 8-weeks of preseason in elite women soccer players. Vertical jumps (squat jump [SJ]; countermovement jump [CMJ]) and Yo-Yo intermittent recovery level 1 test (YOYO-R1) were assessed pre- and post-preseason. A paired sample t-test was used to compare differences between pre and post preseason (Delta%). The level of significance was established at P=0.05. RESULTS: The women soccer players improved the SJ (P<0.001; Delta%=12), CMJ (P<0.001; Delta%=8.5), and YOYO-R1 (P<0.001; Delta%=28.5). There was a body re-composition observed, lower body fat (P=0.004; Delta%=15), higher fat free mass (P=0.001; Delta%=5). CONCLUSIONS: Our results demonstrated that it is possible to develop aerobic and power abilities of elite women soccer players during preseason using an equalized ratio of soccer training and strength-power training schedules.